Evaluation of shortwave and longwave radiation models for mechanistic-empirical pavement analysis. Issue 10 (24th August 2022) - Alam-Khan, Shafkat; Cetin, Bora; Forman, Barton A.; Kutay, M. Emin; Durham, Stephan; Schwartz, Charles W.
ABSTRACT: Pavement temperature is one of the most important factors influencing the performance of flexible pavements. The major components of the Earth's heat balance system are downwelling shortwave radiation (D-SWR) from the sun, downwelling longwave radiation (D-LWR) from the atmosphere, and upwelling longwave radiation (U-LWR) emitted by the warm pavement surface. The Pavement ME Design (PMED) software (AASHTO, 2015 . Mechanistic-empirical pavement design guide–a manual of practice . Washington, DC: AASHTO) computes temperature distributions in the pavement over depth and time using algorithms originally proposed by Dempsey et al. (1985 . Environmental effects on pavements: theory manual . US Department of Transportation, Federal Highway Administration). These algorithms are largely empirical, depend heavily on imprecise corrections for cloud cover, and in some parts contradict atmospheric physics. Improved models for the major radiation components proposed here include: (1) D-SWR values modelled by the MERRA-2 climate re-analysis product from NASA (Rienecker et al., 2011. MERRA: NASA's modern-era retrospective analysis for research and applications. Journal of Climate, 24, 3624–3648); (2) D-LWR modelled using the Idso (1981 . A set of equations for full spectrum and 8-to 14-μm and 10.5-to 12.5-μm thermal radiation from cloudless skies. Water Resources Research, 17, 295–304) empirical parameterisation with a physics-consistent adjustment for cloud cover; and (3) U-LWR calculations without the physics-inconsistent cloud cover adjustment embedded in PMED. The D-SWR and D-LWR radiation models were evaluated via comparisons against ground-based radiation observations at 21 locations in the Solar Infrared Radiations Stations (SIRS) database. The MERRA-2 estimates of D-SWR, although not perfect, were found to agree substantially better than the current PMED models with the ground truth SIRS. The D-LWR fluxes from the Idso (1981 . A set of equations for full spectrum and 8-to 14-μm and 10.5-to 12.5-μm thermal radiation from cloudless skies. Water Resources Research, 17, 295–304) parameterisation were also found to agree substantially better than the current PMED with the ground truth SIRS, with particularly striking improvements for the all-sky (i.e. including clouds) condition. A limited series of flexible pavement performance analyses were conducted to illustrate the potential practical impact of these radiation model changes. The new radiation models produced significantly higher pavement temperatures that lead to substantially higher total rutting, asphalt rutting, and bottom up fatigue cracking. These changes in distress magnitudes must be evaluated in qualitative terms only, as all analyses used the same field calibration coefficients for the distress models. The primary conclusion from this work is that the current radiation models incorporated in PMED are inaccurate and, in some cases, inconsistent with fundamental atmospheric physics. This can have significant impacts on predicted pavement performance. It is recommended that the current PMED radiation models be replaced by the new D-SWR, D-LWR, and U-LWR. New field calibration of the empirical distress models would be required after incorporating the new radiation models.